2005
DOI: 10.1074/jbc.m412552200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phospholipid Binding by Site 3 and Site 4 Toxins

Abstract: It has been shown recently that polypeptide toxins that modulate the gating properties of voltage-sensitive cation channels are able to bind to phospholipid membranes, leading to the suggestion that these toxins are able to access a channel-binding site that remains membrane-restricted (Lee, S.-Y., and MacKinnon, R. (2004) Nature 430, 232-235). We therefore examined the ability of anthopleurin B (ApB), a sea anemone toxin that selectively modifies inactivation kinetics of Na V 1.x channels, and ProTx-II, a spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 34 publications
(47 reference statements)
1
73
1
Order By: Relevance
“…In contrast, dissociation remained a zero-order reaction as expected ( 250 nM ϭ 53.3 Ϯ 3.2 S, n ϭ 3; 500 nM ϭ 41.7 Ϯ 2.2 S, n ϭ 3). ProTx-II also shifts the voltage dependence of gating to more depolarized potentials, indicating that the toxin does not inhibit through a pore-blocking mechanism but, rather, interferes with the energetics of gating (15). Analysis of ProTx-II on steady-state activation and inactivation kinetics revealed that the midpoint of the activation curve shifted by 23 mV in the depolarizing direction, whereas inactivation remained unaffected by the toxin (Fig.…”
Section: Functional Characterization Of Wild-type and Mutant Forms Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, dissociation remained a zero-order reaction as expected ( 250 nM ϭ 53.3 Ϯ 3.2 S, n ϭ 3; 500 nM ϭ 41.7 Ϯ 2.2 S, n ϭ 3). ProTx-II also shifts the voltage dependence of gating to more depolarized potentials, indicating that the toxin does not inhibit through a pore-blocking mechanism but, rather, interferes with the energetics of gating (15). Analysis of ProTx-II on steady-state activation and inactivation kinetics revealed that the midpoint of the activation curve shifted by 23 mV in the depolarizing direction, whereas inactivation remained unaffected by the toxin (Fig.…”
Section: Functional Characterization Of Wild-type and Mutant Forms Ofmentioning
confidence: 99%
“…The cleaved product was then subcloned into an octahistidine version of the pMALc2x vector (New England Biolabs) between EcoRI and HindIII using standard molecular biology protocols. As described previously, two additional N-terminal amino acids derived from a StuI restriction site remain in the ProTx-II coding sequence (15). Site-directed mutagenesis was performed using the QuikChange method (Stratagene, La Jolla, CA) to create all recombinant toxin mutants described in this paper, and all constructs were verified by sequencing.…”
Section: Molecular Biologymentioning
confidence: 99%
See 3 more Smart Citations